The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21873/invivo.12545
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of NRIP1 and LCOR in Endometrioid Endometrial Cancer

Abstract: Background: The aim of the study was to analyze the expression of nuclear receptor interacting protein 1 (NRIP1) and its partner ligand-dependent nuclear receptor co-repressor (LCOR) in endometrioid endometrial cancer and to investigate their association with estrogen receptor (ER), progesterone receptor (PR), Ki-67, clinicopathological parameters and patient survival. Materials and Methods: Immunohistochemical evaluation was carried out to investigate the subcellular expression of NRIP1 and LCOR in endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Flindris et al, finally, have recently reported a very interesting highly significant association between NRIP1 (nuclear receptor interacting protein 1) and Ki67 expression in endometrial cancer (8). In their study, NRIP1 expression was also strongly correlated with myometrial invasion, so that Ki67 expression in endometrial cancer may not only reflect a higher proliferation rate of the tumor cells, but also, indirectly, higher tumor invasiveness.…”
Section: Discussionmentioning
confidence: 77%
“…Flindris et al, finally, have recently reported a very interesting highly significant association between NRIP1 (nuclear receptor interacting protein 1) and Ki67 expression in endometrial cancer (8). In their study, NRIP1 expression was also strongly correlated with myometrial invasion, so that Ki67 expression in endometrial cancer may not only reflect a higher proliferation rate of the tumor cells, but also, indirectly, higher tumor invasiveness.…”
Section: Discussionmentioning
confidence: 77%
“…NRIP1 exerts a carcinogenic effect in various solid tumors [ 48 , 49 , 50 ]. Furthermore, NRIP1 is a classical mutated gene in EC cell lines [ 51 ], and its overexpression is a common cause driving EC and advanced myometrial invasion [ 52 , 53 ]. RNA editing levels of ZNF264 are greatly correlated with the clinical outcome of EC [ 54 ].…”
Section: Discussionmentioning
confidence: 99%